Comparative Research of Managerial Communication In Profit And Non-Profit Romanian Organizations During Covid-19 Times - Corina Daniela BOGHEANU; Iudith Anci KIS; Adela JANSEN; Madlena NEN (Communications of International Proceedings, 2022)
The purpose of this paper is to determine the managerial communication optimizing factors in crisis times, with lenses of assertive communication and empowerment through emotional intelligence. By using the communication skills and empathy, also the relationships' creation ability, one may influence other people's behaviors and judgements. In stressed times, the intensity of fear and hope, truth and fake news, firmness and generosity, decision-making speed and their impact, professional and personal experiences and feelings have unprecedented power. The research is a comparative analysis of adaptive communication in pandemics of a leading market for-profit organization of      one hundred employees in the industrial field, and a national footprint non-profit organization in education. Structured interviews were run with relevant actors, identifying several common elements, like a proactive attitude and resilience. Firstly, the loyalty for organizational vision and mission was respected, doubled by unprecedented transparency and intensity of communication. Secondly, all internal and external stakeholders were addressed, assuring the continuity on short and long-term of the collaboration. Thirdly, all types of available communication methods and channels were used and employees, as well as close collaborators, were accelerated trained in order to maintain the staff performance. The noticed differences were based on factors depending on industry and jobs’ type allowing remote work or not and on the financial power of the organization. The study limitations rely on the small sample of institutions where the research was done.
Keywords: Covid-19 Crisis; Managerial Communication; Emotional Intelligence; Leadership